Kompleksitas Pendidikan Bahasa Indonesia Kelas Tinggi di SDN 132412 Kota Tanjungbalai - Rambe, Riris Nurkholida; Fadilah, Fadilah; Nugraha, Muhammad Nuryansyah; Harahap, Rizki Melinda; Silalahi, Tia Anggraini; Ramadhani, Tivany (TSAQOFAH, 2023)
The goal of language education is to optimize students' skills in communicating correctly and accurately, both orally and in writing. Thus the purpose of this study is none other than to look at the complexity of Indonesian language education for high school students at SDN 132412 Tanjungbalai City. The method used in this research is descriptive and qualitative method. The descriptive method is telling or describing the data collected. The purpose of this method is to replace or describe situations or phenomena that occur in solving real world problems. This method is usually used to study people or objects, conditions or symptoms of a particular population or region. Tanjungbalai 132412 Public Elementary School students were used as research subjects. In addition, the method of collecting evidence or information is done by interviewing the homeroom teacher and the student.